The Internationalization of Chinese Firms: Resource-Based View - MA, JIE (2009)
The internationalization of firms in China has undergone significant development for several decades, but still have some limitations because of resource constraints. This paper discusses Chinese firms’ internationalization with resource-based view framework and identifies the essential resources that Chinese multinationals need to exploit and deploy in developed market for the purpose of addressing their competitive disadvantages. This paper studies the case of Haier which is undergoing a successful resource seeking in the international market. In this study, it is also present a new viewpoint of resource-based theory of a firm based on the data obtained from the case study. It is concluded that four key categories of resources such as Entrepreneur-, Technology Innovation-, Network-, Brand-Specific Resource influence the performance of internationalization. Further, areas for additional research are identified to further deal with the process of the internationalization of Chinese firms.